2016
DOI: 10.1037/adb0000189
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between gambling fallacies and problem gambling.

Abstract: The cognitive model of problem gambling posits that erroneous gambling-related fallacies are key in the development and maintenance of problem gambling. However, this contention is based on cross-sectional rather than longitudinal associations between these constructs, and gambling fallacy instruments that may have inflated this associated by their inclusion of problem gambling symptomatology. The current research re-evaluates the relationship between problem gambling and gambling-specific erroneous cognitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 48 publications
(61 reference statements)
6
56
0
Order By: Relevance
“…The results showed that the variables having the strongest cross-sectional relationship with gambling fallacies were: greater reliance on intuitive thought, a less rational cognitive style, and poorer probabilistic reasoning ability. In addition, adding support to previous studies (e.g., Leonard & Williams, 2016;Yakovenko et al, 2016), gambling engagement was again found to predict gambling fallacy endorsement.…”
Section: Study Three (Chapter Four)supporting
confidence: 75%
See 2 more Smart Citations
“…The results showed that the variables having the strongest cross-sectional relationship with gambling fallacies were: greater reliance on intuitive thought, a less rational cognitive style, and poorer probabilistic reasoning ability. In addition, adding support to previous studies (e.g., Leonard & Williams, 2016;Yakovenko et al, 2016), gambling engagement was again found to predict gambling fallacy endorsement.…”
Section: Study Three (Chapter Four)supporting
confidence: 75%
“…However, unlike previous prospective investigations, gambling fallacy endorsement was not significantly associated with other gambling engagement measures. However, part of the difference has to do with the fact that much larger samples were used by Leonard & Williams (2016) and Yakovenko et al (2016), which allowed the correlations to be significant despite the fact that the magnitudes of the correlations was not markedly higher. Taken together, gambling engagement does seem to play a role in the development and maintenance of gambling fallacies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated the important role cognitive distortions play in both the treatment of and recovery from problem gambling . In addition, with recent insight into the reciprocal nature of the relationship between the cognitive distortions and gambling etiology, earlier screening of potential problem‐gambling behavior and endorsement of gambling‐related cognitive fallacies provides the evidence for the need of earlier intervention which could lead to better treatment outcomes. There are few treatments for veterans with GD that address the psychiatric complexity present among many veterans with GD.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, they are more likely to experience illusions of control, the belief that one can influence the outcome of a chance‐determined event, and the gambler's fallacy, the belief that future outcomes can be predicted on the basis of past outcomes. In a recent longitudinal study, both cross‐sectional and longitudinal analyses provided further evidence of and insight into the relationship between cognitive distortions and the presentation of problem gambling and its bidirectional nature . However, no research to date has investigated the extent to which veterans with GD present with gambling‐related cognitive distortions.…”
Section: Introductionmentioning
confidence: 99%